The Effectiveness of Nursing Interventions Based on King’s Theory: A Systematic Review - Rouhi Balasi, Leila; Elahi, Nasrin; Beiranvand, Samira; Tavakoli, Pouran; Rouhi Balasi, Reyhaneh (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: King’s Conceptual Model and Goal Attainment Theory can applicate as an effective framework in all fields of nursing such practice, education, management and research. The purpose of this study was to evaluate effectiveness of nursing interventions based King's theory. Methods: In this systematic review, the databases as Scopus, Web of Sciences, Pub Med and search engine of Google Scholar have been searched. Then the review has been done in terms of the study criteria, and merely 10 articles have met the criteria. Results: Our findings indicate, the common form of theory that has been applied in articles was goal attainment theory, except in one case. In 40% of the articles, the theory was used in educational fields and 60% were related to the clinical area. Conclusions: According to this systematic review, King's Conceptual System and Theory of Goal Attainment has the potential to give an effective approach for nursing practice and it is recommended that this framework can be used in different clinical situations to attract the patients to better compliance, leading to an improvement in quality of life and reduce complications in patients.